A new generic name to solve the paraphyly of Sticherus C.Presl (Gleicheniaceae, Polypodiopsida) - Lima, Lucas Vieira; Salino, Alexandre; Rouhan, Germinal; Almeida, Thaís Elias (Phytotaxa, 2025)
Gleicheniaceae is an early diverging lineage of leptosporangiate ferns, characterized by pseudodichotomous frond branching. While six genera are phylogenetically supported, Sticherus has been found to be paraphyletic. To resolve this issue, we describe a new genus, Sticheroides gen. nov., to accommodate Sticherus truncatus and S. milnei, based on phylogenetic placement, time divergence depth, and frond architecture. We provide an updated identification key to the genera, descriptions, and comments. Sticheroides diverged from the clade formed by Gleichenia+Stromatopteris+Sticherus approximately 114–117 Mya and is distinguished by buds and rhizomes covered with scales and anisotomic branching. The new genus solves the paraphyly of Sticherus as defined so far, while ensuring nomenclatural stability within Gleicheniaceae.